1983
DOI: 10.1177/00220345830620100501
|View full text |Cite
|
Sign up to set email alerts
|

Neuraminidase-activated Attachment of Actinomyces naeslundii ATCC 12104 to Human Buccal Epithelial Cells

Abstract: The attachment of Actinomyces naeslundii ATCC 12104 to human buccal epithelial cells pre-treated with neuraminidase (sialidase) was evaluated. Both commercial clostridial neuraminidase and neuraminidase preparations from the test strain of A. naeslundii enhanced attachment. The results suggest that the A. naeslundii beta-galactoside-seeking ligand involved in hemagglutination and interbacterial coaggregation also mediates one type of binding to human buccal epithelial cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

1986
1986
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In contrast, a nanH, nanP double mutant had a 53% reduction in its ability to bind to HeLa cells ( Figure 5; Jost et al 2002a, b). These data indicate that the neuraminidases of A. pyogenes play a role in the adherence of this organism to host epithelial cells, probably through exposing cryptic host cell receptors for other A. pyogenes adhesin molecules, as seen with the neuraminidases of S. pneumoniae (Tong et al 1999) and A. viscosus (Saunders and Miller 1983). Lectin-binding studies indicated that the S. pneumoniae NanA neuraminidase-exposed N-acetylglucosamine and D-galactose residues (Tong et al 2002), although the molecular target(s) were not elucidated.…”
Section: Neuraminidasesmentioning
confidence: 77%
“…In contrast, a nanH, nanP double mutant had a 53% reduction in its ability to bind to HeLa cells ( Figure 5; Jost et al 2002a, b). These data indicate that the neuraminidases of A. pyogenes play a role in the adherence of this organism to host epithelial cells, probably through exposing cryptic host cell receptors for other A. pyogenes adhesin molecules, as seen with the neuraminidases of S. pneumoniae (Tong et al 1999) and A. viscosus (Saunders and Miller 1983). Lectin-binding studies indicated that the S. pneumoniae NanA neuraminidase-exposed N-acetylglucosamine and D-galactose residues (Tong et al 2002), although the molecular target(s) were not elucidated.…”
Section: Neuraminidasesmentioning
confidence: 77%
“…Neuraminidase decreases the viscosity of the lung mucus, which may predispose individuals to secondary pneumonia by many of the pathogens listed in Table 2. The purified enzyme in vitro increases the adhesion of oral bacteria to human buccal epithelial cells (47,48 …”
Section: Resultsmentioning
confidence: 99%
“…Type 2 fimbriae are known to be involved in coaggregation with many S. sanguis and S. mitis strains and in attachment to buc cal epithelial cells, but are not involved in adherence to experimental salivary pelli cle, as has been shown for type I fimbriae [Saunders and Miller, 1980;Cisar et al" 1984b;Brennan et al, 1984;Clark, 1985]. If 2-hour plaque can be interpreted to re present initial adherence, the similar pro portions of A. naeslundii and A. viscosus could be hypothesized to be partly due to coaggregation between S. sanguis and A. naeslundii.…”
Section: Discussionmentioning
confidence: 99%